Oral Tumors; Clinicopathological Study among Patients Attending ENT Clinic in Baghdad - Muhsen, Hussein J.; AL-Raheem, Yousif . A (AL-Kindy College Medical Journal, 2009)
Background: Oral tumors are one of the most challenging tumors regarding their good prognosis in early diagnosis and very difficult control in advancing stages. Objectives: To study the prevalence, types and clinical presentation of oral tumors in comparison to other oral lesions among patients attending ENT clinic. Al-Kindy Col Med J 2008 Vol.5(1) Original Article 11 Methods: This study included 534 patients with different oral complains attending ENT clinics in AI-Yarmouk Teaching Hospital, and AI-Kindy Teaching Hospital - Baghdad, in the period from 1st jan1999 till 31th des 2006 (8 years interval). Results: The results of this study showed that the prevalence of malignant lesions was 13.5% (72 out of 534); the males constitute 59.7 % of them. Premalignant lesions constitute only 3.9% (21 out of 534) of patients; the males constitute 66.7 % of them. Benign lesions in 8.6% (46 out of 534); the males constitute 69.6 % of them. Other lesions constitute 74% (395 out of 534); the males constitute 65.8 % of them. Squamous cell carcinoma is the most common malignant tumor (found in 71% of malignant lesions). Conclusions: Most patients are males and the most common manifestation is sore throat. The most common sign of presentation is swelling and the most common histological type of malignant tumors is squamous cell carcinoma (71%). These patients usually attend ENT clinic seeking for simple therapy, we see that it’s the job of the otolaryngologist to diagnose those patients early which has a major influence on prognosi